Profitability and yield response of garlic based cropping systems in Chalan Beel area of Bangladesh - Ali, M K J; Emon, R M; Khatun, M K; Nahar, K; Jannat, S A; Rahman, M M (Bangladesh Journal of Nuclear Agriculture, 2025)
Garlic (Allium sativum) is one of the most extensively grown spice crops in Bangladesh. The garlic- based cropping pattern is gaining recognition as an effective and sustainable agricultural practice. This system maximizes land utilization, enhances soil fertility, and boosts farmers' economic returns. This paper examines the benefits, challenges, and best practices for adopting the garlic based cropping sequence in the Chalan Beel area. The cost of production method was applied to calculate the data. A comparative analysis of existing and improved cropping patterns in medium high land (CP-1) and medium low land (CP-2) highlights significant economic and yield benefits from incorporating garlic-based systems. In CP-1, replacing lentil with Garlic and adopting a high-yielding rice variety increases the total net income from Tk. 75,660 to Tk. 3,02,094, while the BCR rises from 1.16 to 1.74. In CP-2, replacing the fallow period with Garlic and substituting Boro rice with watermelon increase the total net income of Tk. 3,76,664, with an improved BCR of 1.89. The findings underscore the economic viability of garlic-based cropping patterns in enhancing profitability and optimizing land use efficiency. This study assesses the agronomic, economic advantages and offers recommendations for its successful implementation. This cropping pattern seems to be efficient and profitable system for this region. Bangladesh J. Nuclear Agric., 39(1): 129-137, 2025